Gut microbiota alternation with training periodization and physical fitness in Japanese elite athletes - Nobuhiko Akazawa; Nobuhiko Akazawa; Mariko Nakamura; Nobuhiko Eda; Nobuhiko Eda; Haruka Murakami; Takashi Nakagata; Takashi Nakagata; Hinako Nanri; Hinako Nanri; Jonguk Park; Koji Hosomi; et al. (Frontiers in Sports and Active Living, 2023)
IntroductionThe gut microbiome plays a fundamental role in host homeostasis through regulating immune functions, enzyme activity, and hormone secretion. Exercise is associated with changes in gut microbiome composition and function. However, few studies have investigated the gut microbiome during training periodization. The present study aimed to investigate the relationship between training periodization and the gut microbiome in elite athletes.MethodsIn total, 84 elite athletes participated in the cross-sectional study; and gut microbiome was determined during their transition or preparation season period. Further, 10 short-track speed skate athletes participated in the longitudinal study, which assessed the gut microbiome and physical fitness such as aerobic capacity and anaerobic power in the general and specific preparation phase of training periodization. The gut microbiome was analyzed using 16S rRNA sequencing.ResultsThe cross-sectional study revealed significant differences in Prevotella, Bifidobacterium, Parabacteroides, and Alistipes genera and in enterotype distribution between transition and preparation season phase periodization. In the longitudinal study, training phase periodization altered the level of Bacteroides, Blautia, and Bifidobacterium in the microbiome. Such changes in the microbiome were significantly correlated with alternations in aerobic capacity and tended to correlate with the anaerobic power.DiscussionThese findings suggest that periodization alters the gut microbiome abundance related to energy metabolism and trainability of physical fitness. Athlete's condition may thus be mediated to some extent by the microbiota in the intestinal environment.